What is the role for multistakeholder platforms in transboundary basin governance? Distilling lessons from three cases and applying them in the Incomati Basin - Nehring, Ryan; Lautze, Jonathan F.; Mgudlwa, Maliviwe (Informa UK Limited, 2025)
Multistakeholder platforms have become a go-to institutional model for achieving effective and inclusive water governance. With the proliferation of cooperative arrangements at a transboundary scale, there has been a growing number of transboundary river basin multistakeholder platforms. While these basin-wide platforms should contribute to improving water governance, evidence on the structure and impacts of them is scarce. This paper outlines the development of a transboundary multistakeholder platform in the Incomati River Basin in Southern Africa. Learning from experiences in other shared basins, we focus on the multiscale and political aspects of integrating multistakeholder platforms into transboundary basin governance.